Early Childhood Development in Samoa : Baseline Results from the Samoan Early Human Capability Index - Brinkman, Sally; Sincovich, Alanna; Vu, Binh Thanh (World Bank, Washington, DC, 2019)
The Pacific early age readiness and learning (PEARL) program aims to support Pacific Island countries and their development partners in building capacity to design, implement, and monitor evidence-based integrated policies and programs that prepare children and their families for primary school. PEARL’s two focus areas are reflected in its two visions: (1) that all children in the Pacific have access to and benefit from programs in their communities that promote healthy, stimulating, and culturally relevant experiences that prepare them for pre-primary, primary schooling, and life; and (2) all classrooms in the early grades of primary education are equipped with the knowledge and the resources to ensure children become literate in a language they are familiar with, and that they are able to use these skills and knowledge to engage in lifelong learning. This report provides a comprehensive picture of the current status of children’s early development in Samoa, the environments in which children in Samoa are growing up, and how these environments are having an impact on children’s early developmental outcomes. Results produced some expected findings reflecting international evidence, as well as some surprising ones, providing the country with a valuable evidence base on which policy makers and service providers can base their planning around, and policy monitoring and program evaluation can be measured against.